2018
DOI: 10.1186/s13104-018-3740-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and correlates of symptoms of anxiety and depression among young caregivers of cancer patients: a pilot study

Abstract: ObjectivesTo determine the frequency of symptoms of anxiety and depression among the young caregivers of family members with cancer and their correlation with role of gender, age and socio-economic status.ResultsA total of 87.8% of caregivers were between 11 and 16 years of age, with 94.6% reported having support from another caregiver. At least 95% of caregivers reported symptoms of anxiety with a higher predisposition among females. Around 73% of caregivers had low monthly incomes followed by (22.9%) middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, this evidence is not always consistent. While some authors report a high proportion of emotional problems [5], depression and anxiety in young carers [18]; others describe young carers reporting positive rather than negative mental health effects from their caregiving, with only a small subset displaying clinical levels of depression [20]. This lack of clarity in evidence hampers efforts to support and address the mental health needs of young people who provide informal care.…”
Section: Introductionmentioning
confidence: 99%
“…However, this evidence is not always consistent. While some authors report a high proportion of emotional problems [5], depression and anxiety in young carers [18]; others describe young carers reporting positive rather than negative mental health effects from their caregiving, with only a small subset displaying clinical levels of depression [20]. This lack of clarity in evidence hampers efforts to support and address the mental health needs of young people who provide informal care.…”
Section: Introductionmentioning
confidence: 99%
“…As increase in the score obtained from the scale indicates that healthy lifestyle behaviors are performed better. According to the reliability study of the scale, the Cronbach's alpha coefficient was determined as 0.91 (23,24). In our study, the Cronbach's alpha value was found to be 0.93.…”
Section: The Healthy Lifestyle Behaviors Scalementioning
confidence: 53%